2014
DOI: 10.2967/jnumed.113.125880
|View full text |Cite
|
Sign up to set email alerts
|

Transient Ischemic Dilation of the Left Ventricle on SPECT: Correlation with Findings at Coronary CT Angiography

Abstract: Transient ischemic dilation (TID) in the setting of abnormal stress-rest cardiac SPECT myocardial perfusion imaging (MPI) has been linked with increased cardiovascular risk. However, the significance of TID in the setting of an otherwise normal SPECT MPI study has not been clearly established. In this study, cardiac CT was used to evaluate the prevalence of atherosclerotic lesions and the severity of coronary artery stenosis in patients with TID of the left ventricle with or without associated myocardial perfu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 20 publications
(22 reference statements)
0
17
0
Order By: Relevance
“…Halligan et al confirmed the absence of an increase in multivessel disease in patients with TID and extended the results to include no increase in calcium score or extent of atherosclerosis as measured by cardiac CT in 1,553 consecutive patients who underwent a SPECT MPI and cardiac CT within 1 month between 2006 and 2011. (18) The incidence of MACE was also similar. There is potential selection bias in this cohort, however, as the authors could not control for parameters that drove the decision to perform cardiac CT rather than invasive coronary angiography.…”
Section: Contemporary Studies On Tid In Otherwise Normal Mpimentioning
confidence: 64%
See 1 more Smart Citation
“…Halligan et al confirmed the absence of an increase in multivessel disease in patients with TID and extended the results to include no increase in calcium score or extent of atherosclerosis as measured by cardiac CT in 1,553 consecutive patients who underwent a SPECT MPI and cardiac CT within 1 month between 2006 and 2011. (18) The incidence of MACE was also similar. There is potential selection bias in this cohort, however, as the authors could not control for parameters that drove the decision to perform cardiac CT rather than invasive coronary angiography.…”
Section: Contemporary Studies On Tid In Otherwise Normal Mpimentioning
confidence: 64%
“…Given that recent studies show no incremental benefit of TID in this population, these patients can be observed with careful follow-up. (18, 24) Patients with high-risk comorbidities such as known CAD, diabetes mellitus, or chronic kidney disease, have an intermediate risk, and TID may have benefit in this subgroup. (21) However, the majority of these patients will not have obstructive disease on angiography.…”
Section: Tid Clinical Applicationmentioning
confidence: 99%
“…Xu () studied a population with <5% likelihood of CAD and defined the normal limits for transient ischaemic dilatation; the upper limits were 46% for end‐systolic and 23% for end‐diastolic TID in low likelihood of patients with CAD. On the other hand, it has been showed that the presence of TID with otherwise normal SPECT perfusion imaging has benign prognosis (Halligan et al ., ) (Doukky et al ., ). Based on that, information of TID should be interpreted with caution because considerable amount of TID can be observed even without significant myocardial ischaemia.…”
Section: Discussionmentioning
confidence: 99%
“…[123] Initial studies, with the use of exercise thallium-201, noted that the size of the left ventricle is sometime larger on the immediate poststress image than on the 4 h redistribution image; the phenomenon of which was named “TID of the left ventricle.”[1] Many patients with multivessel CAD have been found to have an abnormal TID, making this finding an easily derived and highly specific marker of multivessel critical stenosis with potential important prognostic value. [14] Several mechanisms are considered responsible for TID on nuclear images; these include subendocardial ischemia, temporary systolic dysfunction or myocardial stunning, and/or a true increase in left ventricular (LV) size.…”
Section: Introductionmentioning
confidence: 99%